2003
DOI: 10.2458/azu_jrm_v56i5_guenther
|View full text |Cite
|
Sign up to set email alerts
|

Observations of cattle use of prairie dog towns

Abstract: We investigated the use of prairie dog towns by cattle (Bos taurus) on the shortgrass steppe of northeastern Colorado by conducting surveys of cattle and vegetation from June to August 1999. Cattle presence and behavior were recorded 3 times a week during driving surveys of 15 black-tailed prairie dog (Cynomys ludovicianus) towns. A subset of 3 pastures with prairie dog towns was intensively surveyed twice weekly wherein the habitat and activity of a randomly chosen focal animal was recorded every 6 minutes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
1
10
2
Order By: Relevance
“…All research occurred in pastures with no known history of crop cultivation. Pastures were grazed by cattle at moderate stocking rates (~0.60 animal unit months Á ha À1 ) each year from 15 May to 1 October, where an animal unit month was defined as the equivalent of a 454-kg livestock unit grazing for 30 d. Previous work showed that cattle at this site graze on prairie dog colonies in proportion to their availability within the landscape (Guenther and Detling 2003).…”
Section: Study Areamentioning
confidence: 99%
“…All research occurred in pastures with no known history of crop cultivation. Pastures were grazed by cattle at moderate stocking rates (~0.60 animal unit months Á ha À1 ) each year from 15 May to 1 October, where an animal unit month was defined as the equivalent of a 454-kg livestock unit grazing for 30 d. Previous work showed that cattle at this site graze on prairie dog colonies in proportion to their availability within the landscape (Guenther and Detling 2003).…”
Section: Study Areamentioning
confidence: 99%
“…All sites have been grazed by cattle during the growing season since about 1940. Within the PNG, pastures are grazed at ‘moderate’ rates averaging 1·74 ha per cow per month (Guenther & Detling 2003). Actual grazing intensity varies among pastures because cattle are privately owned and managed.…”
Section: Methodsmentioning
confidence: 99%
“…Actual grazing intensity varies among pastures because cattle are privately owned and managed. Each colony was near enough to its reference site to be grazed by the same herd of cattle, and cattle appear not to prefer or avoid grazing on prairie dog colonies (Guenther & Detling 2003). In 2004, one of the old colonies experienced a plague epizootic and was not sampled that year, and a suitable replacement site was not available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We visually estimated the cover of each species to the nearest 1.0%. Canopy height was measured by placing a lightweight Styrofoam board (20 £ 30 cm) over the Daubenmire frame and measuring the height from the ground to the center of the board (Guenther and Detling 2003).…”
Section: Vegetation Samplingmentioning
confidence: 99%